2013
DOI: 10.1099/ijs.0.049569-0
|View full text |Cite
|
Sign up to set email alerts
|

Frischella perrara gen. nov., sp. nov., a gammaproteobacterium isolated from the gut of the honeybee, Apis mellifera

Abstract: The gut of the Western honeybee, Apis mellifera, is colonized by a characteristic set of bacteria. Two distinct gammaproteobacteria are consistent members of this unique microbial community, and one has recently been described in a new genus and species with the name Gilliamella apicola . Here, we present the isolation and characterization of PEB0191T, a strain belonging to the second gammaproteobacterial species present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 18 publications
(33 reference statements)
5
82
0
Order By: Relevance
“…Our 16S rRNA gene tree placed BiG as a member of Orbales, a bacterial order previously recovered from numerous honey bee and bumble bee species (13). BiG clusters among sequences collected from native and commercially reared bumble bee species from around the world ( (36) shows that BiG clusters within a separate clade from the genus Gilliamella (found in honey bees and bumble bees [13]), Frischella perrara (Gamma-2 of honey bees [37]), and other Orbales species, with strong bootstrap support (95%) (Fig. 1b; see also Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our 16S rRNA gene tree placed BiG as a member of Orbales, a bacterial order previously recovered from numerous honey bee and bumble bee species (13). BiG clusters among sequences collected from native and commercially reared bumble bee species from around the world ( (36) shows that BiG clusters within a separate clade from the genus Gilliamella (found in honey bees and bumble bees [13]), Frischella perrara (Gamma-2 of honey bees [37]), and other Orbales species, with strong bootstrap support (95%) (Fig. 1b; see also Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This bacterium is less abundant than the other two species, with fewer bacteria present in the gut of individual bees, and in some cases, the bacterium is not present at all (5, 9, 12). Interestingly, all three bacteria have so far only been found associated with social bees and form deep-branching phylogenetic lineages exclusive of bacteria sampled from other environments (7,8,13), supporting longstanding symbiotic associations with their host and among each other.Bacterial symbionts frequently mediate interactions by using secondary metabolites, such as nonribosomal peptides and polyketides. These natural small molecules harbor a variety of activities, serving as mutualistic factors (14) Citation Engel P, Vizcaino MI, Crawford JM.…”
mentioning
confidence: 99%
“…In the anterior part of the honey bee hindgut, two gammaproteobacteria, Gilliamella apicola and Frischella perrara, and one betaproteobacterium, Snodgrassella alvi, are the dominant members of this gut community (7)(8)(9). Comparative genomics and functional analyses have recently revealed that S. alvi and G. apicola harbor complementary metabolic pathways, contain diverse sets of genes for symbiotic interactions, and exhibit host-specific colonization patterns (10,11).…”
mentioning
confidence: 99%
“…These three species have been axenically cultured and characterized biochemically and morphologically (15,16). The core microbiota also includes three species of Alphaproteobacteria ("Alpha-1," "Alpha-2.1," and "Alpha-2.2" [7]) and three Gram-positive species ("Bifido," corresponding to Bifidobacterium asteroides [17], and "Firm-4" and "Firm-5" [both Firmicutes: Lactobacillaceae]) (7).…”
mentioning
confidence: 99%